A computational multiscale model of cortical spreading depression propagation. (1st September 2017) - Gerardo-Giorda, Luca; Kroos, Julia M.
Abstract: Cortical Spreading Depression (CSD) is a disruption of the brain homeostasis that, originating in the visual cortex and traveling towards the frontal lobe, temporarily impairs the normal functioning of neurons. Although, as of today, little is known about the mechanisms that can trigger or stop such phenomenon, CSD is commonly accepted as a correlate of migraine visual aura. In this paper, we introduce a multiscale PDE-ODE model that couples the propagation of the depolarization wave associated to CSD with a detailed electrophysiological model for the neuronal activity to capture both macroscopic and microscopic dynamics.